1995
DOI: 10.1042/bj3110189
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytosolic phospholipase A2 in arachidonic acid release of rat-liver macrophages: regulation by Ca2+ and phosphorylation

Abstract: In this study we have verified the existence of a cytosolic phospholipase A2 (cPLA2) in rat-liver macrophages. Stimulation of these cells with phorbol 12-myristate 13-acetate (PMA), zymosan and lipopolysaccharide (LPS), but not with the Ca(2+)-ionophore A23187, leads to phosphorylation of cPLA2 and activation of mitogen-activated protein (MAP) kinase, supporting the hypothesis that MAP kinase is involved in cPLA2 phosphorylation. We show furthermore, that the tyrosine kinase inhibitor genistein prevents the LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…The role of cPLA 2 in regulating arachidonic acid release at basal calcium levels, however, has not been addressed. It has been proposed that arachidonic acid release in PMA-stimulated rat macrophages does not depend on a phospholipase A 2 but on the combined action of phospholipase C and diacylglycerol lipase (56). We now provide evidence that cPLA 2 is essential for arachidonic acid release and eicosanoid production induced by PMA and okadaic acid, which do not mobilize calcium in macrophages.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The role of cPLA 2 in regulating arachidonic acid release at basal calcium levels, however, has not been addressed. It has been proposed that arachidonic acid release in PMA-stimulated rat macrophages does not depend on a phospholipase A 2 but on the combined action of phospholipase C and diacylglycerol lipase (56). We now provide evidence that cPLA 2 is essential for arachidonic acid release and eicosanoid production induced by PMA and okadaic acid, which do not mobilize calcium in macrophages.…”
Section: Discussionmentioning
confidence: 50%
“…Arachidonic acid release under conditions of basal cytosolic calcium have also been reported in different mammalian systems, although the role of cPLA 2 has not been definitively established (21,25,61). In addition, cPLA 2 has been implicated in delayed arachidonic acid release, observed hours after stimulation, when calcium levels would not be expected to remain elevated (3,4,17,26,56). The ability of cPLA 2 to mediate arachidonic acid release without an increase in calcium levels cannot be explained by increased phosphorylation on Ser-505, which is not sufficient for cPLA 2 to mediate arachidonic acid release (17,25,31,36).…”
Section: Discussionmentioning
confidence: 99%
“…In several models, arachidonic acid release has been linked to the influx of extracellular calcium (28 -31). From results using rat liver macrophages, it has been suggested that an increase in [Ca 2ϩ ] i , but not cPLA 2 phosphorylation, is necessary for arachidonic acid release (14). However, our results show that cPLA 2 phosphorylation on Ser-505 is required in macrophages when there is a transient increase in [Ca 2ϩ ] i but that it is not essential when there is a sustained increase in [Ca 2ϩ ] i from extracellular sources as induced by the calcium ionophores.…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, CSF-1 induces cPLA 2 phosphorylation but not arachidonic acid release although it can act synergistically with calcium mobilizing agonists (13). It has been suggested that an increase in intracellular calcium concentration [Ca 2ϩ ] i , but not phosphorylation of cPLA 2 , is essential for arachidonic acid release in rat liver macrophages (14). In platelets, thrombin-stimulated arachidonic acid release does not require phosphorylation of cPLA 2 on Ser-505 (15).…”
mentioning
confidence: 99%
“…After this observation, many groups reported the concomitant activation of MAPK and phosphorylation of cPLA # in stimulated cells [12][13][14][15][16][17]. Several recent reports, however, dissociate cPLA # phosphorylation from MAPK activation.…”
Section: Introductionmentioning
confidence: 99%